Executive dysfunction in patients with spinocerebellar ataxia type 3 - Tamura, Itaru; Takei, Asako; Hamada, Shinsuke; Soma, Hiroyuki; Nonaka, Michio; Homma, Sanae; Moriwaka, Fumio (Journal of neurology, 2018)
The aim of this study was to assess the cognitive functions of patients with spinocerebellar ataxia type 3(SCA3). We examined 15 patients with genetically confirmed SCA3 and 15 healthy control subjects matched for age, years of education, and intellectual ability. We administered verbal memory (word recall and word recognition) and executive function tasks (word fluency test, forward and backward digit and visual span tests, Kana Pick-out Test, Trail Making Test, and conflicting instructions and a Go/NoGo task from the Frontal Assessment Battery). We found that patients with SCA3 had significantly lower scores than the healthy control subjects on the word recall, semantic, and letter fluency, and backward digit span tests, while word recognition was well preserved. The other executive function tests showed preserved functions in the SCA3 group, indicating that visual working memory, and attention and inhibition control were not affected. The patients with SCA3 showed impaired word recall and intact word recognition, and accordingly, episodic memory encoding and storage processes in short-term memory were preserved. In category and letter-fluency tests, impairment was attributable to word-retrieval from semantic memory. Impaired verbal working memory may be involved in the retrieval of verbal information from phonological storage by means of continuous subvocal rehearsal, rather than a deficit in initial phonological encoding. Essential executive dysfunction in patients with SCA3 may be due to damage in the cerebellar cortex–ventral dentate nucleus–thalamus–prefrontal cortex circuits, which are involved in strategic retrieval of verbal information from different modes of memory storage.